Supporting employers in the reserve operational forces era : are changes needed to reservists' employment rights legislation, policies, or programs? - Gates, Susan M., 1968-; McGovern, Geoffrey; Waggoner, Ivan; Winkler, John D.; Pierson, Ashley; Andrews, Lauren; Buryk, Peter (Research report (Rand Corporation), 2013)
Employer Support of the Guard and Reserve (ESGR), a U.S. Department of Defense office (DoD), asked the RAND Corporation to study the implications that using the Reserve Components (RCs) as an operational force can have for employers in view of employment rights protections for RC members. Specifically, ESGR wanted to know whether changes are needed to the Uniformed Services Employment and Reemployment Rights Act (USERRA), 1994 legislation designed to prevent hiring discrimination and bolster job protection for members of the armed forces, including those of the RCs; ESGR support programs; or RC activation and deployment policies, given the increased mobilization of the National Guard and Reserve and the continuing need to balance the rights, duties, and obligations of employers, RC members, and RC members' families. The study involved the review and analysis of existing research and data related to USERRA and the effects on employers of employee absences more generally, an analysis of the 2011 DoD National Survey of Employers, focus groups with employers conducted in 2012, interviews with RC chiefs conducted in 2011, and a legal and legislative history review of USERRA. This report describes key findings from the analysis.